2021
DOI: 10.1093/brain/awab119
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the basal ganglia and indirect pathway neurons during frontal lobe seizures

Abstract: There are no detailed descriptions of neuronal circuit active during frontal lobe motor seizures. Using activity reporter mice, local field potential recordings, tissue clearing, viral tracing, and super-resolution microscopy, we found neuronal activation after focal motor to bilateral tonic-clonic seizures in the striatum, globus pallidus externus, subthalamic nucleus, substantia nigra pars reticulata and neurons of the indirect pathway. Seizures preferentially activated dopamine D2 receptor-expressing neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 89 publications
1
35
0
Order By: Relevance
“…Thus, our findings support the connectivity hypothesis that excitatory anatomic connections of the seizure focus drive seizure spread. This hypothesis is not only limited to the hippocampal circuit as our previous work in frontal lobe spontaneous seizures also supports it (Brodovskaya et al, 2021). Interestingly, we revealed that the propagation pattern is preserved in the lamellar direction throughout the kindling process, while no rapid propagation pattern is observed or emerges in the septotemporal direction.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, our findings support the connectivity hypothesis that excitatory anatomic connections of the seizure focus drive seizure spread. This hypothesis is not only limited to the hippocampal circuit as our previous work in frontal lobe spontaneous seizures also supports it (Brodovskaya et al, 2021). Interestingly, we revealed that the propagation pattern is preserved in the lamellar direction throughout the kindling process, while no rapid propagation pattern is observed or emerges in the septotemporal direction.…”
Section: Discussionsupporting
confidence: 86%
“…To determine whether systemic D2R agonist injection was anticonvulsant, we administered full selective D2R agonist sumanirole (5 mg/kg ip) or normosol as a control. Because sumanirole has a sustained effect for at least 2 h, 6 we had two injection cohorts. In the first cohort, we did three consecutive injections to determine the anticonvulsant effect.…”
Section: Resultsmentioning
confidence: 99%
“…TRAP2 mice were perfused with 4% paraformaldehyde, sliced on a cryostat at 40 µm, immunolabeled with rabbit anti-NeuN (1:500, #24307, Cell Signaling) and rabbit anti-PV (1:500, #ab11427; Abcam), and imaged on a confocal microscope at 10×/.45 numerical aperture (NA) or 20×/.95 NA as described previously. 6 We used ImageJ and Imaris Spots detection tools to count tdTomato-positive cells in D2R agonist-injected versus noninjected mice. We subtracted background and adjusted the threshold to count cells.…”
Section: Immunohistochemistry Microscopy and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Stephen King opined, in The Colorado Kid that , “sooner or later, everything old is new again.” It is one of the delights of science that we can make “old” targets new again, with new approaches that provide greater resolution and heightened precision. In their recent manuscript, Brodovskaya and colleagues 1 examined an “old” set of structures—the basal ganglia, using new approaches to map, with cell-type specific resolution, the pathways engaged by seizures originating in the frontal cortex.…”
Section: Commentarymentioning
confidence: 99%